Konsep Ulumul Quran Muhammad Mafudz al-Tarmas dalam Manuskrip Fath al-Khabir bi Sharh Mifta>h al’Tafsi>r - Zaenatul Hakamah (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2018)
This research reviews the differentiation, uniqueness, and theoretical power that is in Fath al-Khabi>r bi Sharh Mifta>h al-Tafsi>r. This research is a manuscript research by Sheikh Muhammad Mahfudz al-Termasi Pacitan which explain / sharh the book of mifta>h al-Tafsi>r or what is called Alfiyah Ilm Tafsi>r written by Nigerian scholar named Syeih Abdullah ibn Muhammad ibn Uthman ibn Salih al-Niji> ri>. The book is a manuscript that is still in the form of Sheikh Mahfudz Termas’s handwriting, this study uses a philology method that will describe the manuscript and analyze it using several contemporary Qur’anic study theories. This research shows the concept of a unique and systematic ulumul Qur’an offered by Kyai Mahfudz Termas.